A reality check for climate change experiments: Do they reflect the real world?. Issue 10 (4th September 2018) - Knapp, Alan K.; Carroll, Charles J.W.; Griffin‐Nolan, Robert J.; Slette, Ingrid J.; Chaves, Francis A.; Baur, Lauren E.; Felton, Andrew J.; Gray, Jesse E.; Hoffman, Ava M.; Lemoine, Nathan P.; Mao, Wei; Post, Alison K.; et al.
Abstract: Experiments are widely used in ecology, particularly for assessing global change impacts on ecosystem function. However, results from experiments often are inconsistent with observations made under natural conditions, suggesting the need for rigorous comparisons of experimental and observational studies. We conducted such a "reality check" for a grassland ecosystem by compiling results from nine independently conducted climate change experiments. Each experiment manipulated growing season precipitation (GSP) and measured responses in aboveground net primary production (ANPP). We compared results from experiments with long‐term (33‐yr) annual precipitation and ANPP records to ask if collectively ( n = 44 experiment‐years) experiments yielded estimates of ANPP, rain‐use efficiency (RUE, grams per square meter ANPP per mm precipitation), and the relationship between GSP and ANPP comparable to observations. We found that mean ANPP and RUE from experiments did not deviate from observations. Experiments and observational data also yielded similar functional relationships between ANPP and GSP, but only within the range of historically observed GSP. Fewer experiments imposed extreme levels of GSP (outside the observed 33‐yr record), but when these were included, they altered the GSP–ANPP relationship. This result underscores the need for more experiments imposing extreme precipitation levels to resolve how forecast changes in climate regimes will affect ecosystem function in the future.